Validitas Aplikasi Penilaian Sikap Berbasis Android Mata Pelajaran Pendidikan Agama Islam (PAI) - Masruchan Masruchan; Suwarno Suwarno; Muhammad Hatta (Neolectura, 2023)
The 2013 curriculum mandates that psychomotor, emotional, and cognitive domains be included in educational evaluation. Teachers, including those who teach PAI subjects, still struggle with affective or attitude evaluation. In order to determine the validity of the development product in the form of an attitude assessment application, the authors are interested in creating an android-based attitude assessment application for PAI subjects. The ADDIE research and development model method is being used in this project. A total of 50 instructors teaching Islamic religious education courses from 5 distinct madrasahs—MAN 1 Mojokerto, MAN 2 Mojokerto, MA Nurul Islam, MA Al Mas'udy, and MA Al Islamy in Mojokerto Regency—participated in this study. The study took place between January and June 2022. The methods used to acquire the data were observation, interviews, and questionnaires. Both qualitative and quantitative data analysis is used. Data from interviews and observations were analyzed qualitatively, while information from questionnaires was analyzed quantitatively. Based on the evaluation of information technology experts, who gave the development of an android-based attitude assessment application an average score of 4.25, and evaluation experts, who gave it an average score of 4.37, the results demonstrated that it was a very valid application.